A methods engineering study on ACR Furniture Manufacturing Corporation - Baterina, Eunessa A.; Peñalosa, William P.; Velasquez, Katherine May G. (Diliman, Quezon City College of Engineering, 2001)
A methods engineering study was conducted on ACR Furniture Manufacturing Corporation. ACR is a company engaged in the production of sofa beds, sala sets and other home furnishings and foam products. With the use of Streamline Diagnostic Charts, the group was able to identify the problems of the company. The major problems include no method for material handling and storage and inefficient layout. Further analysis and with the use of Ishikawa Diagram, the group was able to identify the root causes of the mentioned problems. These root problems include disorganized working place and storage space, delay in storage of the finished products and improper storage of in-process materials. By focusing on these core problems, the group was able to suggest a alternatives which then combined, solves the major problems identified above. Several alternatives were suggested for inefficiency in layout. Rearranging the cutting tables and sewing machines is one of the alternatives suggested to maximize the working space. The problem may also be solved by the relocation of the cutting machines from certain places. These do not require any costly arrangements and could be easily done by assigning some workers to rearrange the machines after working hours. On the other hand, lack of storage area or space may be solved by the installation of a permanent roofing between the third and fourth building. This will serve as an additional storage space used primarily for the wood frames to protect them from environmental conditions such as rain. This must be done during summer so that when the rainy season comes, the company would not have to worry about the rotting of the woods. Another alternative is to place rotating bins in the working area to serve as a storage for small materials and tools such as nails, knives, etc. These would free up a lot of space and the working place will be more orderly.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis